Expression of heparan sulfate in gastric carcinoma and its correlation with clinicopathological features and patient survival. Issue 2 (19th December 2010) - Lo, Soo-Ling; Thike, Aye Aye; Tan, Soo-Yong; Lim, Tony Kiat-Hon; Tan, Iain Bee-Huat; Choo, Su-Pin; Tan, Puay-Hoon; Bay, Boon-Huat; Yip, George Wai-Cheong
Abstract : Aim: To determine the expression pattern and prognostic value of heparan sulfate in gastric cancer. Method: The 10E4 antiheparan sulfate monoclonal antibody was used to examine the expression pattern of heparan sulfate in tissue microarrays consisting of 162 cases of gastric carcinoma by immunohistochemistry. The immunoreactivities of both epithelial and stromal components of the specimens were examined and analysed statistically for significant associations with clinicopathological parameters, including histological grade of the tumour, extent of cancer infiltration and presence of lymph-node metastases, lymphovascular invasion, perineural invasion, perforation of gastric wall and stromal reaction. The potential use of heparan sulfate as a predictive factor for patient survival was also evaluated. Results: Reduced expression of heparan sulfate in the epithelial component was associated with higher histological grades of gastric cancer as well as the presence of more extensive tumour infiltration. Furthermore, this decrease in heparan sulfate expression was found to be predictive of reduced patient survival after tumour recurrence. Conclusion: The data suggest that heparan sulfate may play an important role in regulating the biology of gastric cancer, and that it may be a useful prognostic marker of this tumour.